Development and application of quechers method for extraction and analysis of polycyclic aromatic hydrocarbons (PAHS) in South African fish samples - Oduntan, Afolake Olufunmilola (My University, 2015)
Polycyclic Aromatic Hydrocarbons (PAHs) are environmental contaminants which are formed during combustion of organic material such as coal, petroleum compounds and meat. Other sources of PAHs include automobile exhaust, coal tar and crude oil. Natural sources of PAHs include volcanoes, forest fires. Some PAHs are known to be carcinogenic and toxic. They are available to aquatic organisms such as fishes through contaminated sediments and other marine organisms. Due to their toxicity, it is essential to study and monitor PAHs in the environment. In this study, the quechers extraction method was developed and optimised for the extraction of 5 PAHs (Naphthalene, acenaphthene, phenanthrene, fluoranthene, and pyrene). The optimised parameters were the extraction speed, extraction time, volume of solvent, type of solvent, the mass of salt (MgSO4), the mass of fish used for extraction, mass of sorbent (PSA) and the type of sorbent used. After optimisation, the optimised QuEChERS extraction method was then compared to the Soxhlet extraction method. Firstly by spiking with different concentration and comparing the recoveries. Recoveries obtained where similar, this shows that the QuEChERS method is efficient for extraction of PAHs. The optimised QuEChERS extraction method and Soxhlet extraction were applied for analysis of PAHs in real fish samples. Fish samples were obtained from two dams, Jericho dam in Mpumalanga and Hartbeespoort dam in Gauteng. The result obtained for both extraction method were compared. The concentration of PAHs obtained for both methods were similar. Naphthalene was not detected in Hartbeespoort dam. The concentration of PAHs in Hartbeespoort and Jericho dam using QuEChERS extraction method range from 0.8 μg/kg to 739 μg/kg and 0.8 μg/kg to 7.4 μg/kg respectively. Acenaphthene and phenanathrene were not detected in all fish sample from Jericho dam, while pyrene was not detected in some of the fish samples from Jericho dam. Application of Soxhlet extraction to real sample gave concentration ranging from 1.9 μg/kg to 908 μg/kg for Hartbeespoort dam and 1.2 μg/kg to 18.7 μg/kg for Jericho dam. High concentration of PAHs was obtained from Hartbeespoort dam.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. Johannesburg 2014
Keywords: Polycyclic Aromatic Hydrocarbons.; Fishes.; Fishs - Effect of habitat modification on - South Africa.